(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
The paper examined challenges of investment in teacher development education in Nigerian Universities. The study made use of secondary data for its analysis. The paper premised on the fact that teacher education programme is directed towards the development of teacher proficiency and competence that would enable and empower the teacher to meet the requirements of the profession and face the challenges therein. In the light of this, the paper observed that challenging factors such as funding and lack of respect for teacher education has been found as what has limited teacher education in Nigeria. This leads to the paper concluding that, achieving quality education would be a mirage if teacher education is not improved and taken cognizance off. The paper suggested amongst others that government should provide adequate funding as well as instructional materials for the training of teachers in the different programme in teacher education in the country.